Acacia auriculiformis dan Eragrostis chariis: Vegetasi Potensial dari Lahan Bekas Tambang Timah Pulau Bangka Sebagai Fitoremediator Pb dan Sn: Acacia auriculiformis and Eragrostis chariis: Potential Vegetations from Tin-Mined Lands in Bangka Island as Pb and Sn Phytoremediator - Eka Sari; Giyanto Giyanto; Untung Sudadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2016)
Lead (Pb) and Tin (Sn) are heavy metals most commonly found in tin-mined lands, Bangka Island. Heavy metal contaminated soil can be remediated by applying phytoremediation technology. This research was aimed to analyze vegetation composition and structure in tin-mined lands, to evaluate Pb and Sn accumulation in soils and tissues of the dominant vegetations, and to determine potential vegetations to be utilized as Pb and Sn phytoremediator. The observation was conducted at reclaimed tin-mined lands (LBTR), unreclaimed tin-mined lands (LBTB), and secondary forest lands as the control. Dominant vegetation was determined by the species-area curve and vegetation analysis using the Square method. Accumulation of Pb and Sn in soil and tissue of the dominant vegetation were respectively determined using Morgan extractant and toxicity characteristic leaching procedure (TCLP). The results showed that soil-Sn was undetected. The total soil-Pb in LBTR and LBTB exceeded its quality standard. The highest level of total soil-Pb was found in LBTR. The content of tissue-Pb and -Sn in the dominant vegetation did not exceed them each normal limits. Acacia auriculiformis in secondary forest and Eragrostis chariis in LBTB were found potential to be utilized as Pb and Sn phytoremediator. Keywords: Acacia auriculiformis, Eragrostis chariis, Pb, phytoremediator, Sn